Coffee Farm Agrotourism Model as Fluctuating Income Solution and Environmental Uncertainty in Kabupaten Bener Meriah and Aceh Tengah - Siti Maimunah; Hamdiah Hamdiah; Yohana Dian Putri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Coffee is a leading commodity and a source of community income where coffee plantations are managed and owned by the community. This study aims to determine the effect of coffee plantation agro-tourism development on the solution of community income fluctuations and environmental uncertainty. This study uses primary data sourced from a questionnaire of as many as 170 respondents conducted by purposive sampling method. This research method uses a causal model survey method using path analysis techniques with Structural Equation Models (SEM). The results of data analysis obtained coefficient and significance values that illustrate that coffee plantation agrotourism has a significant effect on environmental uncertainty with a significant value of 0.000 which means that if coffee plantation agro-tourism is developed, it will be a solution to environmental uncertainty. Furthermore, coffee plantation agro-tourism also significantly affects people's income with a significant coefficient value of 0.000. If coffee plantation agro-tourism is developed, it will solve community income fluctuations. The role of the government has no effect on people's income with a significance value above 0.05 and does not affect environmental uncertainty with a significance value above 0.05. It shows no government influence in the development of coffee plantation agro-tourism. Moderation: The government's role is still fragile, with a negative coefficient value and a significant value greater than 0.05. This means that the government has not played a role in making coffee plantation agro-tourism one of the tourist destinations in Bener and Central Aceh districts. The conclusion is that the development of coffee plantation agro-tourism is a factor that can be used to increase people's income which is currently fluctuating because the coffee harvest influences it. The development of coffee plantation agro-tourism is also a factor that can overcome environmental uncertainty, where farming communities can use coffee fields as gardens that produce coffee fruit and at the same time as agro-tourism that can create new jobs, open up business opportunities and educate visitors about coffee.